Prytanoides, a new myodochine genus to include a new species from Argentina, and new records for Prytanes Distant species (Hemiptera: Rhyparochromidae) - Dellapé, Pablo Matías (2024)
The new genus Prytanoides is described to accommodate the new species Prytanoides prorrectus from Argentina. Its relationship with the presumably closely related Prytanes is discussed. The distributional range of four Prytanes species is also extended: Prytanes formosus and Prytanes foedus are recorded for many provinces in Argentina; Prytanes oblongus is recorded from Ecuador for the first time; and Prytanes tumens from Mexico. For each species, we provide a colour habitus of the adult, together with photographs of the male genitalia of the new genus and species.